EDUKASI LIMBAH MAKANAN, BAHAYA TERHADAP KESEHATAN DAN LINGKUNGAN SERTA POTENSI PEMANFAATANNYA UNTUK MENGURANGI FOOD WASTE - Muhammad Nuzul Azhim Ash Siddiq; Pakki, Irfansyah Baharuddin; Junaidin, Junaidin; Sinthary, Venna; Rozi, Fahrul; Majiding, Chaidir Masyhuri; Wahyuni, Leny Eka Tyas; Nisaa, Nur Rezky Khairun; Anggreini, Putri; Wirawanti, Ika Wirya; Khuzaimah, Ummi; Rahmadani, Aulia Tia; Sari, Mila Warma (Jurnal Abdi Insani, 2024)
Bukit Merdeka Village has great potential for the development of pineapple commodities; however, the utilization of pineapple peel waste remains suboptimal and is often regarded as mere waste. The management of food waste has become a critical issue due to its negative impact on health and the environment, where food waste is often discarded without further utilization. The objective of this community service activity is to educate the public about the dangers and potential benefits of food waste, with the hope of reducing waste, increasing economic welfare through innovation, and encouraging the people of Bukit Merdeka Village to better understand and optimize the use of food waste creatively and productively. This activity was conducted through lectures and interactive discussions involving all members of the PKK in Bukit Merdeka Village. Participants were also asked to take pre-tests and post-tests to measure their understanding before and after the education. There was a significant increase in the post-test results compared to the pre-test, with the average score of participants rising from 56.0 ± 3.2 to 84.6 ± 1.7. These results indicate that the education provided successfully improved participants' understanding of the dangers of food waste and how to utilize it. This educational activity successfully raised awareness and improved community skills in managing food waste, as well as opened economic opportunities through the utilization of pineapple peel waste.